Quiet time variability over Arecibo and Jicamarca during SSWs - Chau Chong Shing, Jorge Luis (2010)
Diapositivas presentadas en el 2010 CEDAR Workshop, University of Colorado, Boulder, CO, 20-25 June 2010.